Praktek Perataan Laba Ditinjau dari Faktor Ukuran Perusahaan, Profitabilitas dan Leverage Operasi pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia - Susilowati, Luky (Universitas Brawijaya, Indonesia, 2010)
Income Smoothing Practice expected can give the influence advantage to the stocks value and management performance. There are 3 factors which influence the Practice Income Smoothing that's size of the firm, profitability, and leverage operation. Base description above this research purpose to analyze the influence of size of the firm, profitability, and leverage operation of the firm to Income Smoothing Practice in the food and beverage companies that are listing in Bursa Efek Indonesia. This research use the secunder data from financial statement of company food and beverage companies that are listing in Bursa Efek Indonesia period 2005 up to 2007 There are 16 food and beverage companies as sample selected with purposive sampling technique. These data Analyzed by Logistics Regression, because The Dependend variable ( Y) have two category iIf Y = 1 (it means company have apply the income smoothing) and if Y = 0 ( it means company have not apply the income smoothing ). The Result of this research have been concluded that the size of the firm have an effect to income smoothing, while profitability and leverage operation are not significant to income smoothing, Detail discussion, implication and limitation of this research will be explained under consideration following.